Changes in adaptive anthropological characteristics in Tuvan youth due to socio-economic factors - Batsevich , Valery A.; Mashina , Darya A.; Krasil’nikova , Vera A.; Yasina , Oksana V.; Permiakova, Ekaterina Yu. (The New Research of Tuva, 2021)
The article is a comparative study of the total body sizes and diameters of limb segments in the student population of different regions of Tuva, given that the adaptive balance between human body and the environment is now set against the background of serious changes in social and humanitarian factors. In 2015-2019, we collected anthropological data of students aged 17 to 26. The work was carried out at Tuvan State University, Kyzyl, according to a unified methodology. The previous dataset collected in 1976-1978 among the indigenous population in Todzhinsky, Mongun-Taiginsky and Erzinsky rayons was used for comparison, with only data for youth under 26 included into the sample. In order to improve its representativeness, the contingent born and living in different regions of Tuva was grouped by macro-region: Western, Southern, Eastern and Central. The absence of statistically significant differences in total body sizes (with the exception of girls’ chest circumference) among modern students living in different macro-regions allows us to conclude that changes have been happening in a relatively uniform way, even though the macro-regions are different in both geographical and socioeconomic sense. It should be noted, however, that those living in the western part of Tuva have shown a slightly larger value of all total body sizes in students of both sexes. An intergroup comparison of Tuvan students surveyed 40 years ago gave a slightly different result: significantly higher values were confirmed for the body height of young males and females living in the southern macro-region. The results obtained may be an indirect proof of the intensification of ontogenetic processes in the population of this part of the republic. This is also confirmed by the accelerated rates of previously described age-related changes in the skeletal structure of the hand. A similar trend was also recorded for the width of the distal epiphyses of human limbs. With an insignificant number of notable differences between macro-regions of the republic, a picture of secular positive shifts in the value of indicators is clearly recorded. No intergroup variation in the size of the diameters of the distal epiphyses has been recorded. Based on the ecological studies of such populations, one can confidently assert that they display features of accelerated rates of biological growth and aging.